Нfйдите значение выражения -р(4+р)+(р-2)(р+2) при р=3/4

zeka27 zeka27    2   25.04.2019 03:34    0

Ответы
Эленедмонд Эленедмонд  25.04.2019 04:50
P(4+p)+(p-2)(p+2)-4*p-p^2+p^2-2^2-4*p+4-4*3/4+4-3+4=1ответ: 1
ПОКАЗАТЬ ОТВЕТЫ
фирдавс6 фирдавс6  25.04.2019 04:50

 - p(4 + p) + (p - 2)(p + 2)

при

p = \frac{3}{4}

 - \frac{3}{4} (4 + \frac{3}{4} ) + ( \frac{3}{4} - 2)( \frac{3}{4} + 2)

( - \frac{3}{4} ) \times 4 \frac{3}{4} + ( - 1 \frac{1}{4} ) \times 2 \frac{3}{4} =

 = ( - 3 \frac{9}{16} ) + ( - 3 \frac{7}{16} ) = - 7

ответ :

 - 7

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра